(untitled) (Doctor Virtualis, 2024)
Since its origins, alchemy has had to deal with the problem of order. His eccentricity compared to other medieval knowledge posed questions about his collocation and the nature of the object he was looking for, the philosopher’s stone. This article presents the attempt, made by the doctor Pietro Bono da Ferrara, to embed alchemy in the school scientific system. In his work, the Pretiosa Margarita Novella, he uses syllogism to order the treatment of alchemy, the subalternatio to place it within the system of sciences and the concept of forma specifica to describe the philosopher’s stone and insert it in metals’ generation process. In this way, Bono conceives alchemy as a science referring to two orders, the natural one of metal generation, in which it operates, and the divine one, to which he must appeal to find the philosopher’s stone, which are complementary to each other since they both have their origin in God.